Correlation of Outdoor Education With Student's Aggressive Attitudes - Wawan Junresti Daya; Egi Septian Saputra; Lilis Komariyah; Sufyar Mudjianto (Journal of Physical Education For Secondary Schools, 2021)
The purpose of this study was to determine the relationship between outdoor education and aggressiveness between students who have done outdoor education activities and students who have never done outdoor education activities for SMA 8 Bandung students. The approach uses quantitative descriptive and the method used in this research is ex post facto, data was obtained using the Bush and Perry Aggression Questionery instrument, with a sample of 104 class VI students divided into two groups, sampling using purposive sampling technique, data collection tools. in the form of a questionnaire with a questionnaire distribution event via google form. The results of the study were analyzed using the SPSS 26 application, with the independent sample t test. The results of this study indicate that the group that has done outdoor education activities has a lower level of aggressiveness compared to the group that has never done outdoor education activities